Способ измерения износа коллекторов и контактных колец электрических машин - Бекишев Р. Ф. Рудольф Фридрихович; Чиндяскин В. И. Владимир Иванович; Данекер В. А. Валерий Аркадьевич; Качин С. И. Сергей Ильич
опубл. 30.04.86